2016 46th European Microwave Conference (EuMC) 2016
DOI: 10.1109/eumc.2016.7824367
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz microstrip elevated stack antenna technology on GaN-on-low resistivity silicon substrates for TMIC

Abstract: Abstract-In this paper we demonstrate a THz microstrip stack antenna on GaN-on-low resistivity silicon substrates (ρ < 40 Ω.cm). To reduce losses caused by the substrate and to enhance performance of the integrated antenna at THz frequencies, the driven patch is shielded by silicon nitride and gold in addition to a layer of benzocyclobutene (BCB). A second circular patch is elevated in air using gold posts, making this design a stack configuration. The demonstrated antenna shows a measured resonance frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Heights of both dielectrics (single and stack antenna) are optimized to produce better antenna performance; stack dielectric is evaluated using air and BCB for better antenna performance. This study provides an extension of our previous work [15] and [16] where a single patch antenna and rectangular-circular stack antenna was demonstrated. From these studies, we showed that a rectangular-circular stack antenna gave an improved fabrication result at BCB and stack height of 5 flm with gain, directivity and radiation efficiency as high as 3.4 dB, 8.3 dB and 32% respectively.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Heights of both dielectrics (single and stack antenna) are optimized to produce better antenna performance; stack dielectric is evaluated using air and BCB for better antenna performance. This study provides an extension of our previous work [15] and [16] where a single patch antenna and rectangular-circular stack antenna was demonstrated. From these studies, we showed that a rectangular-circular stack antenna gave an improved fabrication result at BCB and stack height of 5 flm with gain, directivity and radiation efficiency as high as 3.4 dB, 8.3 dB and 32% respectively.…”
Section: Introductionmentioning
confidence: 56%
“…The fabrication process of the proposed integrated antenna in this study is related to our previous work [16]. First, 200 nm ShNi4 was deposited onto GaN-on-LR Si using ICP-CVD deposition.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication process of the proposed technology in this study is related to our previous work [6]. First, 200 nm Si 3 Ni 4 was deposited onto GaN-on-LR Si substrate using ICP-CVD deposition on the mesa floor, where the transistor active region was etched away.…”
Section: Materials and Device Technologymentioning
confidence: 99%